The Children are Our Future. Issue 1 (January 2015) - Kelly, Michelle M.
<x xml:space="preserve">Abstract</x> We are excited to introduce the first special topics series in celebration of MCN's 40th anniversary. Each issue of MCN in 2015 will feature a special clinical issue of interest to nurses who practice in the maternal child setting. Our first topic is Chronic Illness in Children.